(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he present paper discusses the deinition of fascism used by the historian Jean Meyer in his book entitled El sinarquismo, el cardenismo y la iglesia 1937- 1947. By providing a quick overview of existing research on the subject, it points out the great variety of deinitions and points of view based on various studies. In order to address the question of the fascist character of synarchism, the paper suggests a close look at the discourse of the Unión Nacional Sinarquista. he present study takes the perspective of the common denominators of fascism and relies on Hélgio Trindade’s work on Brazilian integralism and investigates those points of the synarchist ideological discourse which allow us to relativize and discuss critically why Jean Meyer excluded synarchism from the list of fascist movements.